RECYCLE OF ACTIVE MATERIAL CATHODE LINI1/3CO1/3MN1/3O2 FROM SPENT LI-ION BATTERY WITH ORGANIC ACID LEACHING FOLLOWED BY OXALATE CO-PRECIPITATION PROCESS - Refly, Septia
Lithium ion battery waste, in the form of anodes, cathodes, separators, electrolytes and also outer cases contain heavy metals such as Co, Mn, and Ni which can be reused through recycling. Battery waste is predicted to be increased up to 25 billion in 2020 is also one of the reasons for the importance of recycling. This study reports the recycling of active material cathode from spent lithium ion battery with the leaching process using citric acid and ascorbic acid followed by coprecipitation using oxalic acid. This research consists of four steps: (1) discharge the battery and pretreatment of the cathode, (2) leaching with acid, (3) coprecipitation, and (4) resynthesis of cathode material. Pretreatment was carried out in the form of scrubbed cathode material, immersion in NMP solution, washing, calcination, and grinding with ball milling. Based on the analysis using the X-Ray Diffractometer (XRD) instrument and Energy Dispersive X-Ray Spectroscopy (EDX), the cathode material used in recycling is LixNi1/3Co1/3Mn1/3O2 (NCM) layer structure with a ratio of Ni:Co:Mn = 1:1:1. The calcination at a temperature of 800 ?C for 2 hours cannot change the material structure to be better, but it causes phase changes to spinel, which is indicated by the appearance of fields (220) and (422). Morphological analysis using Scanning Electron Microscope (SEM) shows that NCM particles were spherical which were not uniform size and agglomerated. The particle size of the material is reduced from 500-900 nm to 100-400 nm after grinding. Citric acid and ascorbic acid are used as leaching agents for NCM cathode active material. Leaching of the active material cathode with ascorbic acid agents has several advantages compared to citric acid added sucrose as reductant, including higher efficiency, less mass of residue produced, and faster leaching time. Ascorbic acid acts as a mild reduction and can reduce transition metals to a more soluble form, so it does not require additional reducing agents. The optimal condition of experiments with leaching agents in the form of ascorbic acid is the acid concentration of 1.25 M with a time of 30 minutes and at a temperature of 70 ?C. Leaching metal ions can be deposited through the oxalate coprecipitation process. Analysis using XRD shows that the precipitates are MC2O4?2H2O (M = Co, Mn, Ni). Based on X-Ray Fluorescence (XRF) analysis, the composition of Ni, Co, and Mn elements changes from 1:1:1 (before recycling) to 1:1:0.8 in oxalate precipitation with less composition of Mn than other transition metals. This is related to the bonding of complex compounds between Mn and organic acid chelation that are stronger than others and the high solubility of MnC2O4. The re-synthesis of cathode active material or R-NCM was carried out by a solid state process using a mixture of coprecipitation material from oxalate and lithium acetate which was then calcined at a varied temperature of 780 ?C-950 ?C. The results of the analysis using XRD instruments showed the material structure of R-NCM synthesized with calcination temperature >800 ?C having a sharp peak and no impurity peak was detected. R-NCM 900 ?C has the best structural parameters with low cation mixing and well ordered of layers. The morphology of R-NCM 900?C material is flaky with a smooth surface and has clear boundary lines when analyzed using SEM. In addition, the R-NCM 900 ?C has better electrochemical properties than others with an Rct value of 42.01 ? and an initial discharge capacity of 104.3 mAh / g (0.2 C). After a cycle of 50 times, the retention capacity of 70.76% was obtained. The formation of the re-synthesized NCM cathode material which has characteristics close to the new battery shows that the recycling process has been successfully carried out.